東北亞四國英語教育政策之比較 Comparison of English Education Policies in East Asian Countries - 陳浩然 Hao-Jan Chen; 鄭雅双 Ya-Shuang Cheng; 郭亭吟 Ting-Ying Kuo; 林欣儀 Hsin-Yi Lin (National Taiwan Normal University, 2020)
本研究主旨為分析臺、中、日、韓四國之國中小英語政策，解析臺灣2030年雙語國家政策之可行性。透過文獻整理，爬梳四國之國中小英語課程之起始年齡、授課時數、教學方法、單字量、本國籍英語教師與外籍師資、教科書與未來英語教育政策等八大面向，經由比較四國英語政策之相似處與相異處，提供意見供相關政策參酌。研究發現，除了日本於2020年起從國小五年級開始上英語課，臺、中、韓三國之英語政策皆將英語課的起始年齡調整為國小三年級，英語課的教學法皆改為使用以溝通為導向之教學法為教學的核心理念。本研究針對臺灣現行國小英語政策提出五點建議：一、臺灣在國小階段的單字量可再斟酌增加；二、臺灣在國中階段的英語課總時數可調整；三、運用AI人工智慧科技於英語教學中；四、建立更健全的英語師資培訓系統；五、需建立謹慎的外籍師資遴選制度與配套措施。 This study examined the English education policies for elementary and junior high schools in Taiwan, China, Japan, and South Korea to evaluate the feasibility of practicing the "Bilingual Nation by 2030" policy in Taiwan, and the English education policies in these countries were compared. This study focuses on the following eight aspects: the starting age of English education, total English lesson hours, English teaching methodology, assigned English vocabulary, English teacher training, native-English-speaking teacher recruitment, textbooks and teaching materials, and future policy. This study provides two major observations: First, three of the aforementioned countries begin English lessons in Grade 3. However, Japan begins in Grade 5. Second, all of the countries currently employ a communicative approach as their English teaching method. This study further provides five suggestions for future policy: First, more advanced English vocabulary should be taught at the elementary school level. Second, the number of English lesson hours for students should be increased. Third, English teachers in Taiwan should utilize artificial intelligence in their teaching of English. Fourth, training courses for English teachers should be improved. Finally, the processes of recruiting and supporting English teachers from foreign countries should be planned appropriately.